Women Leadership: Advancing with or without his support. - MATZIOURI, APOSTOLIA (Advances in Social Sciences Research Journal, 2021)
The present paper is built on data collected from our PhD thesis which addressed the burning issue of Women Leadership and which took the form of a census in the region of Western Macedonia and Thrace, which consists 10,7% of the total Greek territory and 5,7% of the Greek population respectively. More specifically, the information provided here resulted from the investigation of one of the seven topics that constituted our questionnaire and by which we tried to figure out the personal life of women-leaders in the Greek educational system, how they manage/cope with their multiple roles and responsibilities, whether their spouses are supportive (and if so how) or competitive. As with all studies, there are areas that I have been unable to tackle. One such area is the multidimensional issue of maternity. The latter will be exposed analytically in a forthcoming article.